Pengaruh Iklim Psikologis Dan Keterlibatan Kerja Terhadap Organizational Citizenship Behavior (Studi Kasus Pada PT Phalosari Unggul Jaya Jombang) - Mochammad Handika Setiawan; Ronny Malavia Mardani; Etty Saraswati (UNIVERSITAS ISLAM MALANG, 2023)
Abstract One of the most important factors in organizational success is OCB behavior. Workers with very high Organizational Citizenship Behavior will go beyond what the company expects. This behavior can be motivated by a desire to actively help colleagues so that employees can work more efficiently in terms of time and effort. The purpose of this study is to see how the psychological climate and work involvement affect the behavior of organizational members. All employees of PT. Phalosari Unggul Jaya Jombang was transformed into a population of 70 respondents using the questionnaire method. Route is used as an analytical technique in this study. According to the conclusions of this study, the psychological environment and work involvement have a positive effect on the behavior of organizational members. This study also found that the psychological environment has a variety of positive and significant effects on the behavior of organizational members.This research was conducted at PT. Phalosari Unggul Jaya Jombang. So the purpose of this research is to investigate and examine the impact of Psychological Climate and Work Participation on Organizational Citizenship Behavior. A total of 70 employees were sampled. The sample strategy was random sampling, and data collection was carried out by distributing statement questionnaires with a 4-point Likert scale, namely